BEHAVIOURAL ADAPTATION OUTPACING STRUCTURAL INTEGRATION: AN EXPLANATORY SEQUENTIAL MIXED-METHODS STUDY OF ORGANIZATIONAL RESTRUCTURING IN THE MEDICAL DEVICE INDUSTRY - Niko Abdurrahman; Santi Novani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Purpose: This study examines about employee adaptation on commercial reorganization in an Indonesian medical device company organization transformation from an Operating Unit-based structure to a strategic cluster model, and explains why adaptation was uneven across employee groups. Methodology: An explanatory sequential mixed-methods design (QUAN → QUAL) was applied with 15 ADKAR survey questions which completed by 73 respondents (90.1% of company population), then followed by 20 participants interview analyzed thematically through Role Theory and integrated via joint display. Findings: Awareness (M = 3.406) and Knowledge (M = 3.384) were the weakest ADKAR dimensions, while Ability (M = 3.881) and Reinforcement (M = 3.712) were strongest. Awareness differed significantly across role-change groups, and Knowledge (β = .232, p = .042) and Ability (β = .305, p = .009) predicted Reinforcement. Behavioural adaptation advanced faster than cognitive understanding and structural integration, sustained by employee agency and local leadership rather than mature systems. Originality: The study applies ADKAR and Role Theory as complementary lenses for examining employee adaptation during commercial restructuring in the medical device industry and proposes the TRACKS implementation framework. Implications: Commercial restructuring demands purposeful attention to transformation direction, role clarity, alignment routines, capability building, knowledge management, and sustained reinforcement.